Pengaruh Pendapatan Orang Tua terhadap Status Gizi Anak Usia 4-5 Tahun pada Masa Pandemi COVID-19 - Aziza, Nurul Aziza; Mil, Silvie (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2021)
The COVID-19 pandemic in Indonesia has occurred since the end of 2019, which impacts parents' income and the fulfilment of children's nutrition. This study aims to determine the effect of parental income on the nutritional status of children aged 4-5 years in Koja District, North Jakarta, during the COVID-19 pandemic. The research method uses quantitative research with a population consisting of children aged 4-5 years in Koja District, North Jakarta. Sampling using random sampling technique, so that the respondents of this study amounted to 77 respondents. Data analysis used linear regression of 2 variables. Estimation of validity and reliability was carried out to determine the quality of the questions. The results showed that there was an effect of parental income during the COVID-19 pandemic on the nutritional status of children aged 4-5 years in Koja District, North Jakarta, with a significance value of 0.000 which was smaller than 0.05 and based on the significance test with the t-value formula, the result was 5.359 greater than t-table of 1.995. The coefficient value of the two variables shows a value of 0.277 or 27.7% of parental income affecting the nutritional status of children during the COVID-19 pandemic. The declining income of parents in the Koja Subdistrict, North Jakarta, during the COVID-19 pandemic can affect the availability of food and the fulfilment of balanced nutrition for children every day, which impacts the nutritional status of children. This research contributes to the understanding that policymakers, in particular, need to pay serious attention to the development of children's nutrition during the COVID-19 pandemic.